Ethnoscience-based Digital Comic on Plant Material for Grade IV Elementary School Students - Rofiqoh, Dita Aminatur; Kiptiyah , Siti Maryatul (Universitas Pendidikan Ganesha, 2024)
There is minimal use of innovative learning media in schools, especially at the elementary school level, even though students need help with learning media to understand the material presented by the teacher. Included in Plant material in class IV science subjects. The aim of this research is to develop digital comic learning media with ethnoscience nuances using plant materials. This development uses the ADDE model. The subjects of this research were 1 material expert, 1 learning media expert, 1 practitioner, namely the teacher. The test subjects were 28 class IV students. Data collection methods are observation, interviews, questionnaires and tests. The data collection instruments are in the form of questionnaires and test questions. The data analysis techniques are qualitative descriptive analysis, quantitative and inferential statistics. The results of the research, namely the results of the validity test of digital comic media based on assessments from material and media experts supported by teacher and student responses, show that the validity value of the press is very high and feasible, with an average percentage value of 92%. The effectiveness test results using digital comic press show that the media is effective. The results of the T-test show that there is a significant difference in student learning outcomes before and after media use. It was concluded that digital comic learning media with ethnoscience nuances based on plant material is suitable for use and is effective in improving student learning outcomes.